2023
DOI: 10.21203/rs.3.rs-2567484/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of socioeconomic activities on water quality in Hainan Island, south China

Abstract: Water quality is intimately related to the livelihood of the numerous people, and affects the development and operating benefits of various industries in society. This study clarifies the effects of human-driven economic activities on inland water quality in Hainan Island, and reveals relationships between water quality and tourism on the island. Based on previously monitored data, this study uses a static Bayesian network and radial basis function neural network (RBFNN) to model and predict the future water q… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Comparing the average values of the indicators of the Wanquan River water quality with the Class III water quality standard in the Environmental Quality Standard for Surface Water (GB3838-2002) [28], we found that the overall water quality of the Wanquan River basin is good, with the average values of all indicators meeting the Class III water quality standard. Compared with Ma's research on the water quality of Wanquan River in 2012-2015, the water quality of Wanquan River decreased from Class II to Class III in 2021, which may be closely related to the development of tourism in this area [31]. In terms of the exceedance rate, Hg was the most serious element, reaching 54%, followed by TN and TP (both 17%) and NH 4 + -N and COD Mn (both 13%).…”
Section: Statistical Characteristics Of Water Quality In the Wanquan ...mentioning
confidence: 69%
“…Comparing the average values of the indicators of the Wanquan River water quality with the Class III water quality standard in the Environmental Quality Standard for Surface Water (GB3838-2002) [28], we found that the overall water quality of the Wanquan River basin is good, with the average values of all indicators meeting the Class III water quality standard. Compared with Ma's research on the water quality of Wanquan River in 2012-2015, the water quality of Wanquan River decreased from Class II to Class III in 2021, which may be closely related to the development of tourism in this area [31]. In terms of the exceedance rate, Hg was the most serious element, reaching 54%, followed by TN and TP (both 17%) and NH 4 + -N and COD Mn (both 13%).…”
Section: Statistical Characteristics Of Water Quality In the Wanquan ...mentioning
confidence: 69%